Pengaruh Efisiensi Kerja, Efektifitas Sistem Informasi Akuntansi, Penggunaan Teknologi Informasi dan Kepuasan Pengguna Sistem Informasi Akuntansi Terhadap Kinerja Individual di PT. POS Indonesia (Persero) Kantor Pos Jambi - Afrizal; Annisa Dewi P; Ilham Wahyudi (Magister Ilmu Akuntansi Universitas Jambi, 2020)
This study aims to determine the effect of work efficiency, effectiveness of accounting information systems, use of information technology and satisfaction of accounting information system users on individual performance at PT. Pos Indonesia (Persero) Jambi Post Office. The total sample of the study was 30 employees at PT. Pos Indonesia (Persero) Jambi Post Office. Data analysis was performed by multiple linear regression analysis and hypothesis testing using the t test and f test methods. The results of this study indicate Work Efficiency, Effectiveness of Accounting Information Systems, Use of Information Technology and User Satisfaction of Accounting Information Systems affect the Individual Performance at PT. Pos Indonesia (Persero) Jambi Post Office. Work efficiency affects individual performance at PT. Pos Indonesia (Persero) Jambi Post Office. The effectiveness of the accounting information system does not affect individual performance at PT. Pos Indonesia (Persero) Jambi Post Office. The use of information technology affects individual performance at PT. Pos Indonesia (Persero) Jambi Post Office. Accounting information system user satisfaction affects individual performance at PT. Pos Indonesia (Persero) Jambi Post Office.